Political Parties Reform In Developing The Competence And Professionalism Of The Legislative Members Of The House Of Representatives Of The Republic Of Indonesia (DPR RI) - Antonio, Renville; Wijoyo, Suparto; Abrianto, Bagus Oktafian; ., Achintya; Negara, Dharma Setiawan; ., Lufsiana (Journal of Ecohumanism, 2024)
PT Pembangkitan Jawa-Bali (PJB), in developing its company, does many things, such as innovating which incidentally is believed to be able to encourage a company to improve its economic performance. One form of innovation carried out by PT PJB is partnering with several universities in Indonesia. The collaboration is expected to be able to build synergies between agencies through the empowerment of facilities and human resources. This research aims to determine the relationship between inter-organizational partnerships on corporate innovation (incremental innovation type) and determine the relationship between inter-organizational partnerships on corporate innovation (radical innovation type). This research is a research with a quantitative approach using statistical analysis tools in testing hypotheses. To measure the relationship between organizational partnership and innovation, this research uses an ordered probit model approach. The research uses the inter-organizational partnership variable as the independent variable along with several other control variables. The research uses data obtained from the results of questionnaires have been distributed to several employees from various levels randomly from PT PJB. Furthermore, the research also uses data obtained from the results of researchers’ observations of key informants have been selected. Partnerships between organizations (with educational institutions) can contribute to company performance. Company performance is described through the birth of innovation (both incremental and radical types). The research indirectly implies the statement that partnerships between organizations can affect the company’s performance through the innovations developed within the company. Furthermore, the research also seeks to create an effective partnership design in generating company innovation. The limitation of this research is data source of this research is only based on PT PJB, in order to the future an analysis of partnerships with educational institutions can be carried out on the performance of other companies. The novelty of this research is focus to analyze the relationship of partnerships with educational institutions on the performance of companies, especially in PT PJB which has not been carried out by other studies.